2009
DOI: 10.1016/j.jcrc.2009.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prediction potential of an in silico computer model of intracranial pressure dynamics

Abstract: Objective: Traumatic brain injury (TBI) frequently results in poor outcome, suggesting that new approaches are needed. We hypothesized that a patient-specific in silico computer model of ICP dynamics may predict the ICP response to therapy. Design: In silico model analysis of prospective data. Stetting: 16-bed pediatric intensive care unit in a tertiary care academic hospital. Patients: 9 subjects with severe TBI undergoing ICP monitoring (7M/2F, age range 3-17 years). Interventions: Random changes in head-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Several works have been published attempting to either predict the onset of ICP crisis events or to forecast future ICP values themselves with limited success (17)(18)(19). The closest work to this study is that of Güiza et al (8).…”
Section: Discussionmentioning
confidence: 96%
“…Several works have been published attempting to either predict the onset of ICP crisis events or to forecast future ICP values themselves with limited success (17)(18)(19). The closest work to this study is that of Güiza et al (8).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, on average increasing CVP led to increase in ICP, which is reported previously in the literature as occurring after a loss of compliance (22,23). Nonlinear models of ICP dynamics have previously been proposed which specifically model the logarithmic relationship between intracranial volume and pressure (24,25) and also incorporate the effect of cerebral autoregulation through linear transfer functions (26)(27)(28)(29)(30). However, parameter estimation in nonlinear systems is much more involved than estimating linear system parameters because of the nonconvexity of the loss function.…”
Section: Discussionmentioning
confidence: 74%
“…More sophisticated analyses using longer time interval data and other entropy calculations in the ECG tracing have subsequently been reported as predictive. In the area of traumatic brain injury, Wakeland et al 40 have reported on the feasibility of an in silico model of intracranial pressure dynamics. Together these represent examples of the use of advanced monitoring technology to provide in silico determination of physiological signals and predictions.…”
Section: Newer Monitoring and Variablesmentioning
confidence: 99%